Why do women choose to undergo oocyte aspiration without sedation or analgesia? - Daniella Gilboa; Liron Seidman; Polina Kimiagarov; Avia Noni; Ravid Doron; Daniel S Seidman (Bioscientifica, 2021)
Objective: Oocyte pick-up (OPU) is a painful but essential part of in-vitro fertilization (IVF) that is usually performed under sedation and analgesia (SaA). Our aim was to study that why some women decide to undergo OPU without SaA? Methods: This was a prospective study using patient questionnaires and the standardized 7-item generalized anxiety disorder (GAD-7) score. The patients were asked to assess the pain experienced during OPU using a visual analog scale (VAS). The study sample was a convenience sample of 100 healthy women undergoing OPU at our unit with or without SaA. Results: Women who chose to undergo OPU without SaA were significantly more likely to express the fear of anesthesia. A high pain score (VAS ≥ 6) was reported by significantly more patients who underwent OPU without SaA than with SaA. Yet, 98% of the patients who underwent OPU without SaA stated that in future IVF cycles, they would still choose to undergo OPU without SaA. More patients had high anxiety scores among those who underwent OPU with than without SaA. Conclusions: Women who chose to undergo OPU without SaA reported more often fear of anesthesia. Although these women experienced significantly more pain during OPU, almost all of them suggested that they would still choose to undergo OPU without SaA. Increased anxiety, as expressed by higher GAD-7 scores, was not associated with a tendency to choose SaA during OPU. The option of OPU without SaA seems to be an acceptable option for selected women.